MOTIVASI PEMBERIAN DAN PEMILIHAN MP-ASI YANG TEPAT PADA BAYI 6-24 BULAN DI KOTA PEKALONGAN - Radiati Moviana; Siti Munawaroh (LPPM STIKES Muhammadiyah Kendal, 2021)
This study aims to determine the motivation for breastfeeding and the practice of choosing complementary feeding for children 6-24 months. The design of this research is a cross sectional study conducted in three posyandu in Pekalongan City from July to August 2021. The respondents were 42 mothers with children 6-24 months. The results showed that 71.43% of mothers had good motivation to give complementary feeding and the practice of choosing complementary feeding in more than half of the mothers was good (59,52%). There is a significant relationship between the motivation of giving omplementary feeding to mothers with the practice of choosing complementary feeding for mothers (p<0,05), but there is no significant relationship between education and income of the mother's family with the choosing complementary feeding practices on mothers (p>0,05).